THE ROLE OF ADAPTIVE POTENTIAL OF YOUTH IN CONDITIONS OF SOCIAL ANXIETY - Atabekyan , L.E. (Modern Psychology, 2021)
The article examines the impact of dynamic changes in political, socioeconomic conditions on the life of youth. In such a situation, young people show signs of anxiety, social insecurity and pessimistic views on the future. Profound changes are taking place in the formation of motives for life, in primary needs, social positions and life values, leading to an exacerbation of the need for security and, at the same time, to a limitation of its satisfaction, which is the most important condition for normal life, development, selfaffirmation and self-expression of young people. The psychological safety of young people is ensured through socio-psychological adaptation due to the adaptive potential. As a result of the study, the features of the perception of social anxiety in young people and the manifestation of adaptive potential in extreme conditions were revealed. A comparative analysis of similar phenomena in the CIS countries, Europe and Israel was also carried out.